Acknowledging and Supplanting White Supremacy Culture in Science Communication and STEM: The Role of Science Communication Trainers - Callwood, Karlisa A.; Weiss, Marissa; Hendricks, Rose; Taylor, Temis G. (Frontiers in Communication, 2022)
Racism remains a root cause of underrepresentation of Black, Indigenous and Latinx scholars across STEM. It also contributes to a lack of diversity in science communication, the types of science stories that are told, and the communities science communicators seek to engage. Racism is omnipresent in STEM, from education to research to science communication (SciComm), because STEM institutions operate within a culture systematically privileging Whiteness, i.e. a White supremacy culture (WSC), that dictates the norms and practices that most in these fields heedlessly accept and replicate. In this Perspective, we acknowledge the ways in which SciComm and SciComm training perpetuate WSC and examine how SciComm trainers can use their power to dismantle it. SciComm trainers pioneer new methods of sharing ideas and influence the culture of STEM, so are uniquely situated to bring about systemic change to address these problems in SciComm, STEM, and society, starting with four core themes for action: 1) Authentic Interrogation, Acknowledgement, and Accountability; 2) Representation; 3) Culturally Responsive Practice; and 4) Inclusion. We also describe our current work, which builds upon the Key Traits of Inclusive SciComm identified by leaders in the field, to co-create a framework to guide authentic, culturally competent, and inclusive SciComm. The draft framework integrates the Key Traits across spheres of influence (e.g. self, interpersonal, community, institution, society: politics & culture), with the ultimate goal of using SciComm to supplant WSC across these spheres of influence, with new co-created norms centering minoritized scholars, science communicators, and audiences in STEM.